THE EFFECT OF DEPRESSION AND ANXIETY IN CHILDREN - Kahveci, Müedin; Baki, Esra (International Scientific Journal Vision, 2023)
In recent years the universities have been focusing much attention on quality assurance. This paper features a look at higher education’s quality, an initial analysis of academic expectations in higher education system and challenges, on some of the key trends based on updated data and recommendations for the universities. This paper will explore about the key drivers for the Macedonian universities that should be pursuing in relation to the Quality Assurance in the Higher Education, Digitally Enhanced Learning and Teaching, Research-based Knowledge and Open Science, Smart Environments and Education, Tools, Methods and Methodologies in Quality Assurance, Innovation-reasoning, Sustainability, and Process Improvement. The North Macedonia must look ahead and offer an excellent knowledge-based and value-based universities while promoting improved values, sustainability performance and well-being of the global community through promote the free circulation of knowledge and gaining a competitive advantage. It will depend on the three factors: creating of quality assurance framework at the universities (consists of a contemporary model of student-centered learning, open and inclusive university, structural and effective cooperation between higher education institutions, public and private sector, and citizens, and founded on the principle of social responsibility), hope-based university leadership and well-structured program funding.